Women and wildlife trafficking : participants, perpetrators and victims - Agu, Helen U.; Gore, Meredith L., 1977- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This volume examines women and wildlife trafficking via a bespoke collection of narratives, case studies and theoretical syntheses from diverse voices and disciplines. Wildlife trafficking has been documented in over one hundred and twenty countries around the world. While species extinction and animal abuse are major problems, wildlife trafficking is also associated with corruption, national insecurity, spread of zoonotic disease, undercutting sustainable development investments and erosion of cultural resources among others. The role of women in wildlife trafficking has remained woefully under-addressed, with scientists and policymakers failing to consider the important causes and consequences of the gendered dimensions of wildlife trafficking. Although the roles of women in wildlife trafficking are mostly unknown, they are not unknowable. This volume helps fill this lacuna by examining the roles and experiences of women with case studies drawn from across the world, including Mexico, Cameroon, the Central African Republic, South Africa and Norway. Women can be wildlife trafficking preventors, perpetrators, and pawns; their roles in both facilitating wildlife trafficking are considered from both a supply and a demand viewpoint. The first half of the book assesses the state of science, offering four different perspectives on how women and wildlife trafficking can be studied or evaluated. The second half of the book profiles diverse case studies from around the world, offering context-specific insight about on-the-ground activities associated with women and wildlife trafficking. This book will be of great interest to students and scholars of wildlife crime, conservation, gender studies, green criminology and environmental law. It will also be of interest to NGOs and policymakers working to improve efficacy of efforts targeting wildlife crime, the illegal wildlife trade, and conservation more broadly"--
OCLC-licensed vendor bibliographic record.
Keywords: Wildlife crimes; Wildlife smuggling; Women; Conservation of natural resources; NATURE / General; NATURE / Animals; NATURE / Ecology